ANALISIS DAN PERANCANGAN SISTEM MANAJEMEN RUANG KULIAH DI UNIVERSITAS KRISTEN INDONESIA - Manalu, Risma Uly (Jurnal Dinamika Pendidikan, 2015)
This research is motivated by the aim to be a reference in the manufacturing room management information system in UKI. Analysis and Management System Design Lecture Hall (Room Management) is one of room management system that serves to regulate the use of the room automatically so that the room can be used more optimally. it will also save the costs. Therefore, room for the Manage applications are made so that it can implement Information technology service management in which it can help efective handling arrangements room usage and efficient in Christian University of Indonesian to support the development of the institution. While the benefit to be achieved in the making of this thesis is that if the design of this system has been implemented, it will save money, because the room is used optimally.Keywords : System, Classroom.